Emergency department thrombolysis improves door to needle times. Issue 6 (20th October 2004) - Corfield, A R; Graham, C A; Adams, J N; Booth, I; McGuffie, A C
Abstract : Objective: To identify the effect on door to needle (DTN) time of moving the site of thrombolysis delivery from the coronary care unit (CCU) to the emergency department (ED). To ascertain if moving the site of thrombolysis enables appropriate use of thrombolysis. Design: Prospective cohort study. Setting: CCU and ED of a 450 bed Scottish district general hospital without on-site primary angioplasty. Participants: Primary site for thrombolysis of patients presenting to the hospital with ST elevation MI (STEMI) moved from CCU to ED on 1 April 2000. Study patients who had a confirmed STEMI and/or received thrombolytic therapy before this date were defined as the pre-change group; those who were diagnosed as STEMI and/or received thrombolytic therapy after this date were defined as the post-change group. Statistical analysis: Mann-Whitney test was used to compare medians and χ 2 test for categorical data. Results: 1349 patients were discharged from CCU with a diagnosis of STEMI or received thrombolysis in the ED or CCU between April 1998 and April 2002. There were 632 patients in the pre-change group and 654 patients in the post-change group. Sixty three patients were excluded. Median DTN time for the pre-change group (321 thrombolysed patients) was 64 minutes and median DTN time for the post-change group (324 thrombolysed patients) was 35 minutes, a median difference of 25 minutes (95% CI for difference 20 to 29 minutes, p<0.0001, Mann-Whitney U test). A total of 37 patients were thrombolysed but did not have a final diagnosis of STEMI. Conclusion: A significant reduction in DTN times accompanied this change in practice in this hospital.